Adherence to the Mediterranean Diet during the COVID-19 national lockdowns: a systematic review of observational studies - Della Valle, Petra Giulia; Mosconi, Giansanto; Nucci, Daniele; Vigezzi, Giacomo Pietro; Gentile, Leandro; Gianfredi, Vincenza; Bonaccio, Marialaura; Gianfagna, Francesco; Signorelli, Carlo; Iacoviello, Licia; Odone, Anna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: During the COVID-19 pandemic, many countries adopted restrictive measures to mitigate infection spread, which might have influenced people’s lifestyle and dietary habits. We conducted a systematic review to evaluate the impact of national lockdowns on adherence to the Mediterranean Diet (MD).Methods: Studies were identified searching Medline, Embase, Web of Science, and the Cochrane Library. Studies published until 4th May 2021 were included. We only considered studies reporting original data from quantitative analysis and assessing changes in adherence to the MD, using validated dietary scores, or in consumption of MD food items. Data extraction, pooling, and quality appraisal of included studies were conducted following the PRISMA guidelines.Results: Forty-two studies were retrieved. After screening, 12 studies met inclusion criteria and were included in the review, of which 4 (33%) were longitudinal studies. Six (85.7%) of the seven studies that measured changes in MD adherence before-during lockdown reported an increase (rate of change of high-adherence to MD ranged between +3.3% and +21.9%). Evidence indicates that consumption of MD food items increased during lockdown but is heterogeneous in study design, quality, and findings.Conclusions: Our results suggest adherence to the MD during lockdown might have increased in some settings, while the determinants of such a trend are to be further explored. We raise awareness of the need to research further the impacts and long-term consequences of COVID-19 containment measures on dietary and lifestyle habits.